Consolidating the Recovery : Seizing Green Growth Opportunities - World Bank (Washington, DC: World Bank, 2022)
The Latin America and the Caribbean region is consolidating its recovery from the COVID‐19 crisis, but the road ahead poses challenges: The damage inflicted by the pandemic on education and poverty require redress; new variants may appear; rising global inflation presents new policy dilemmas; and the long‐standing reform agenda needed to lay the foundations for renewed and inclusive growth remains pending. Further, the global context is evolving rapidly. Over the medium term, the tragedy unfolding in Ukraine will affect the region through unpredictable channels. Over the longer term, increased global alarm over the pace of climate change raises new policy issues. The region’s contribution to greenhouse gases is modest and can be reduced, but the impact of climate change on its people and productive sectors will require significant adaptation. The good news is that LAC’s unique endowments positions it well to seize emerging green growth opportunities if well‐managed. A key message is that improving the region’s capability to adapt and innovate needs to be placed at the center of both the growth and greening agendas and can generate synergies between them.